Assessment of Level of Acceptability of Papaya Brownies (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Brownies are made with healthy canola oil, which is high in monounsaturated fats and may improve your cholesterol levels. Carica papaya(papaya) is rich in vitamins and minerals. It helps food digestion. Adding papaya as one of the ingredients of original brownies will make papaya brownies. The mixture of papaya and original brownies resulted in a sweet and soothing aroma. This study used an experimental design. The respondents were selected randomly. The researchers utilized the survey questionnaires in collecting the data. The respondents assessed the papaya brownies into the variables. In terms of presentation, the respondents obtained a weighted mean of 4.095, with the verbal interpretation of acceptable. In terms of aroma, the respondents obtained a weighted mean of 3.93, with the verbal interpretation of acceptable. In terms of taste, the respondents obtained a weighted mean of 4.23, with the verbal interpretation of acceptable. In terms of competitiveness, the respondents obtained a weighted mean of 4.325, with the verbal interpretation of acceptable. In terms of nutritional value, the respondents obtained a weighted mean of 4.23, with the verbal interpretation of acceptable. The total weighted mean was 4.1, with the verbal interpretation of acceptable. Papaya brownies were highly acceptable by the respondents. This experiment will obtain a much better product that can be sold and compete for the price of original brownies.
Keywords: papaya, brownies